A preliminary study to understand the effects of mask on tinted face cosmetics. Issue 5 (2nd March 2021) - Yokoyama, Emilie; Udodaira, Kumiko; Nicolas, Alexandre; Yamashita, Eri; Maudet, Aurelie; Flament, Frederic; Velleman, Damien
Abstract: Background: The recent COVID‐19 pandemic has generalized the use of face mask in public area, and it is now common to wear it for long hours. But face mask interfere with cosmetics, and key concerns for tinted products are staining of the mask and degradation on face. Consumers have modified beauty routine by a decrease of makeup, but are now expecting new products adapted to face mask. Little is known about the mechanisms that affect most the makeup under the face mask, so that further studies are needed to develop adequate evaluation methods and products. In this study, the color transfer on mask and makeup degradation on face are assessed through a mixed approach of consumer and instrumental evaluation. Materials and Methods: Two tinted face products (A and B) were applied by half face on 11 Japanese women, who conducted real‐life activities with a face mask during 4 hours. Panelists evaluated the stain of their face mask by visual assessment, while the makeup degradation on face was evaluated by color measurement by instrumental method. Results: No difference was observed between the two products for lasting on face, but consumer evaluation showed a better resistance of product A for color transfer on mask. Conclusion: The mix of instrumental and consumer evaluation is a promising way to evaluate the makeup degradation on face and color transfer on mask, which are two key factors to develop mask resistant makeup products.